Social Work for Female Migrant Workers in Japan: From Interviews of Pregnant Technical Intern Trainees and Technical School Students - Hanako Okawara (Budapest International Research and Critics University, 2023)
In Japan, labor shortages have become a serious problem owing to the low birth rate and aging population. Despite the growing expectations of foreign workers, migrant workers’ rights are not fully guaranteed. And in recent years, issues related to pregnancy and childbirth has become a major focus of attention. In this paper, the female migrant workers refer to the technical intern trainees, specified skilled workers and technical school students who stay in Japan for the purpose of making money. In order to analyze the social support required by pregnant migrant workers during their stay in Japan, 11 foreign workers and students who became pregnant during their stay in Japan were interviewed. We analyzed the difficulties they experienced and the support they sought from the perspectives of language barriers and culture and system. The analysis revealed that the difficulties experienced by female migrant workers are complex and intertwined, with multiple difficulties occurring simultaneously. And gender issues in Japanese society and the sending system in their home countries had a strong influence. Some of the support they sought required institutional reform, while others could be provided by people close to them. This is an exploratory research study. I plan to study the various aspects of this issue in-depth in the future.